Lipid Peroxidation Indices at Different Stages of Experimental Burn Disease After Application of â€œCryochorâ€ Preparation - Klimenko, N. A.; Subbota, N. P.; Netâ€™ukhaylo, L. G. (Problems of Cryobiology and Cryomedicine, 2008)
The indices of lipid peroxidation at experimental burn disease on the background of â€œCryochorâ€ preparation use have been studied. It has been established that introduction of â€œCryochorâ€ significantly reduced the lipid peroxidation activation at burn disease and contributed to earlier normalization of its indices.